Yield behaviour of high-density polyethylene: Experimental and numerical characterization. (March 2019) - Manaia, João P.; Pires, Francisco A.; de Jesus, Abílio M.P.; Wu, Shenghua
Abstract: In this work, the yielding response of high-density polyethylene (HDPE) under different stress states and strain rates was experimentally examined and the ability of classical yield criteria to capture their deformation response assessed. A series of biaxial loading tests (pure shear, combined shear and tension/compression, pure tension/compression) using a designed Arcan testing apparatus were performed. In order to investigate a wider range of stress states, flat and cylindrical notched specimens with different curvature radii were also tested. The predictive ability of the Von Mises and the Drucker-Prager yield criteria are compared against the acquired experimental data. The Drucker-Prager yield model allowed an improved description of the available experimental results, demonstrating the need to account for pressure dependency in the yield model's formulation for semi crystalline polymers. Some differences observed may be attributed to the third invariant stress tensor effects. The evolution of stress triaxiality and Lode angle parameters with equivalent plastic strain were extracted from simulations with Drucker-Prager yield criterion. The results show sensitive stress state dependency of the plastic yielding behaviour, which can be attributed to different combinations of stress triaxiality and Lode angle parameters. Also numerical simulations show that there is variation of the stress triaxiality and equivalent plastic strain along the cross section and the location of the maximum plastic strain and maximum stress triaxiality in the specimens are located at the centre of the specimens. Highlights: HDPE yield response under different stress states and strain rates is examined. Biaxial loading tests are used to investigate a wide range of stress states. The predictive ability of von Mises and Drucker‐Prager yield criteria are assessed. The Drucker‐Prager yield model allows an improved description of the available data. Yield behaviour is sensitive to stress triaxiality and Lode angle parameters.